2019
DOI: 10.1002/arch.21597
|View full text |Cite
|
Sign up to set email alerts
|

Ambient temperature‐mediated enzymic activities and intestinal microflora in Lymantria dispar larvae

Abstract: To understand how ambient temperature affect the gypsy moth larvae, and provide a theoretical basis for pest control in different environments. Fourth instar gypsy moth larvae were incubating for 3 hr at 15℃, 20℃, 25℃, 30℃, 35℃, and 40℃, respectively. Afterward, digestive and antioxidant enzyme activities, total antioxidant capacity, and intestinal microflora community were analyzed to reveal how the caterpillars respond to ambient temperature stress. Results showed that both digestive and antioxidant enzymes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 66 publications
(75 reference statements)
1
4
0
Order By: Relevance
“…Proteobacteria is associated with diverse metabolisms such as decomposition, fermentation of complex sugars, and the production of vitamins and degraded aromatic compounds, boosting their hosts' absorption of nutrients 49 . Previous study show that Proteobacteria dominate the gut microbiome of Gypsy moths 50 , Bombyx 51 and cotton bollworms 52 , similar findings also have been reported in many other species of insects in the family Cerambycidae 53 , 54 . The aforementioned studies suggested that Proteobacteria are widely found in gut microbiota of insects and the dominant role of Proteobacteria in the insect gut microbiota may be a distinctive feature of insect gut microbiota composition.…”
Section: Discussionsupporting
confidence: 84%
“…Proteobacteria is associated with diverse metabolisms such as decomposition, fermentation of complex sugars, and the production of vitamins and degraded aromatic compounds, boosting their hosts' absorption of nutrients 49 . Previous study show that Proteobacteria dominate the gut microbiome of Gypsy moths 50 , Bombyx 51 and cotton bollworms 52 , similar findings also have been reported in many other species of insects in the family Cerambycidae 53 , 54 . The aforementioned studies suggested that Proteobacteria are widely found in gut microbiota of insects and the dominant role of Proteobacteria in the insect gut microbiota may be a distinctive feature of insect gut microbiota composition.…”
Section: Discussionsupporting
confidence: 84%
“…Gut microbiota of 218 insect species in 21 orders are generally dominated by Firmicutes (62.1%) and Proteobacteria (20.7%) ( Yun et al 2014 ). For example, Proteobacteria and Firmicutes are amongst the dominant flora in the intestinal tract of lepidopteran insects, such as Plutella xylostella , Lymantria dispar , Helicoverpa armigera, Spodoptera littoralis, Ectropis obliqua , E. grisescens and Bombyx Mori Rajan et al 2020 , Shinde et al 2019 , Xia et al 2017 , Zeng et al 2019 , Chen et al 2016 , Wang et al 2020 ). Proteobacteria and Firmicutes are also dominant in the intestinal bacterial community of other insects, such as Bactrocera tau , Ceratitis capitata , Procecidochares utilis and Lutzomyia longipalpis of Diptera , Anophora glabripennis of Coleoptera and Schistocerca gregaria of Orthoptera ( Behar et al 2008b , Dillon et al 2010 , Gouveia et al 2008 , Prabhakar et al 2013 , Schloss et al 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, three replicates were evaluated by gut microbial 16S rDNA sequencing. Procedures from DNA extraction to Illumina MiSeq sequencing were performed following our previously described methods (Zeng, Shi, Shi, et al, 2019). Sequencing was performed by MajorBio (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously documented that the gut microbial community in Lymantria dispar asiatic is regulated by environmental temperature (Zeng, Shi, Guo, et al, 2019), dietary pH (Zeng, Shi, Shi, et al, 2019), and avermectin stress (Zeng et al, 2020). Previous studies have suggested that gut microbial communities in insects contribute to various biological processes, including pheromone production, pesticide degradation, vitamin synthesis, and pathogen prevention (Reeson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%